FIVE DECADES OF ACHIEVEMENT MOTIVATION RESEARCH IN ELT: A SYSTEMATIC LITERATURE REVIEW (Malaysian Journal of Learning and Instruction, 2024)
Purpose – There is an absence of systematic review papers in the achievement motivation theories literature. In terms of currentresearch trends, English learning motivation is gaining attention as a determiner of success in FLA. Hence, this review aims to trace thetrends in the empirical studies on achievement motivation theories and tools, ranging from 1970 to 2022.Methodology – With a focus on theories, diversity of research participants, and practical ELT-related issues addressed by previousresearchers, this paper applied the PRISMA Systematic Review Protocol to offer a comprehensive synthesis of 91 empirical studieson theories of achievement motivation.Findings – The majority of the published studies were from China and Iran. There was also a large number of studies conducted on tertiary-level learners. Structural equation modelling was found to be the most widely used analysis. In addition, technology-assisted learning is the current trend in achievement motivation research.Significance – This paper offers new insights into the existing achievement motivation literature and identifies the research gaps.This study recommends more studies on expectancy-value theory including in-depth qualitative studies involving culturally diversepopulations and experimental research to develop more effective pedagogical approaches and expand the current understanding ofachievement motivation.